Green leaf lipid extract as a yield stress modifying emulsifier in reduced-fat chocolate - Price, Ruth J (2021)
Chocolate is a composite material of sugar and cocoa particles, sometimes also containing milk powder, in a crystallised fat phase of mostly cocoa butter. As a melt above 40°C, chocolate represents a highly-filled suspension, often formulated close to the maximum packing fraction, especially in the case of lower-fat recipes. Emulsifiers are added to control the rheological properties of chocolate through adsorption at the hydrophilic sugar surfaces, thus inhibiting aggregate formation in the hydrophobic continuous phase. The most commonly applied emulsifier is lecithin (E322). It reduces the viscosity of chocolate and can lower its yield stress. However, polyglycerol polyricinoleate (PGPR, E476) has a much more substantial yield stress lowering effect, unique amongst food-grade emulsifiers. Unfortunately, PGPR is label adverse, perhaps due to its unfamiliar and chemical-sounding name; PGPR has an E-number, and even though lecithin also does, its name is often used in the ingredients list instead, as consumers are more familiar with or even approve of “lecithin”; or perhaps consumers reject it due to the fact that it is “processed” from castor oil. Therefore, the overall aim of this PhD research was to determine a natural alternative that provides a similar yield stress lowering effect. To achieve this goal, the research set out to analyse five commercially available PGPR samples with observationally reported differences in yield stress lowering efficacy, generating analytical data to validate the empirically reported difference in functionality and analysing molecular make-up in order to understand the molecular characteristics that are present in more efficient PGPRs. This new knowledge was then exploited to select a natural molecule possessing the identified molecular properties and yield stress lowering properties comparable with PGPR. Initially, a chocolate model consisting of a 65% (wt) sugar-in-oil suspension, where the oil was pre-treated to remove naturally present surface-active molecules, and a rheology protocol to obtain yield stress data for these suspensions, with and without added emulsifier, was developed. The rheology protocol developed comprised the concentric cylinder geometry to perform a shear stress sweep from high to low stress values and data analysis to compute the Herschel-Bulkley (H-B) yield stress value to allow sample comparison. Applying the commercial PGPR samples at 0.3% (wt) (total sample weight) in the chocolate model revealed that the PGPRs could be separated into those more or less efficient at reducing yield stress, although all PGPRs reduced the yield stress significantly compared to the baseline samples with no added PGPR. The impact of PGPRs on the interfacial tension between treated oil and water was then investigated as a way of interrogating their surface-active character. It was found that the H-B yield stress values were directly proportional to critical micelle concentration data, determined from equilibrium interfacial tension values between water and the chocolate model oil phase with PGPR added at a range of concentrations. The data inferred that the PGPRs that were more efficient at lowering the yield stress probably had a larger hydrophilic head group and straight hydrophobic tails, thus enabling reverse micelle formation at a lower concentration of PGPR. Further analysis via electrospray ionisation-mass spectrometry and size exclusion chromatography revealed that the five PGPR samples were virtually indistinguishable from each other regarding their range of molecular weights. As a verification of this finding, analysis using 13C nuclear magnetic resonance on two samples, the least and most efficient yield stress reducing PGPR samples, showed that the polyricinoleate chain lengths appeared identical. Finally, transmethylation of the samples followed by gas chromatography-mass spectroscopy revealed that a significantly greater amount of ricinoleic acid molecules were present at the terminus of the polyricinoleate chains of the least efficient PGPR sample. Therefore, it was hypothesised that hydroxyl groups at the end fatty acid are attracted to the hydrophilic sugar causing the hydrophobic chain to fold back on itself. The long length of the polyricinoleate chain extending into the continuous phase has been shown in previous research to be essential in the yield stress reducing abilities of PGPR; therefore, any restriction on this chain is detrimental to its functionality. Since most natural polar lipids lack ricinolic acid, the molecular criterion selected to identify a possible alternative to PGPR was the large headgroup configuration of a glycerol-based molecule that separates the acyl chains; acylated monogalactosyl diacylglycerol (acyl-MGDG). Purified acyl-MGDG is commercially not available, so it was obtained in two ways. The enzyme identified as responsible for forming acyl-MGDG, named AGAP-1, was acquired and multiplied using recombinant protein expression technology. This enzyme was used to convert commercially available MGDG and DGDG into acyl-MGDG, validated by high-performance thin-layer chromatography (HPTLC). Only a very small quantity could be obtained, not allowing conclusive statements to be made concerning yield stress lowering efficacy. Alternatively, cocoa leaves were collected from cocoa farms in the Côte D’Ivoire, and the Eden Project biodomes, UK, and mechanically stressed to trigger the formation of acyl-MGDG. HPTLC revealed that both the stressed and the control cocoa leaf lipids contained acyl-MGDG and other acylated galactolipids. The presence of acyl-MGDG without mechanical or biotic stress has not been shown before; however, the leaves showed other signs of lipid breakdown with lower amounts of galactolipids, chlorophyll and carotenoids than expected for a leaf. It may be that the creation of acyl-MGDG is naturally occurring in all senescing leaves, whether or not they have had biotic or abiotic stress applied. The leaf lipids applied to the chocolate model at 0.15% (wt) showed a yield stress lowering ability that was statistically similar to 0.3% (wt) PGPR. This finding is promising for food-grade emulsifier development and one which deserves further development.